1992
DOI: 10.1111/j.1432-1033.1992.tb17185.x
|View full text |Cite
|
Sign up to set email alerts
|

A reinvestigation of the pre‐steady‐state ATPase activity of the nitrogenase from Azotobacter vinelandii

Abstract: The pre-steady-state ATPase activity of nitrogenase has been reinvestigated. The exceptionally high burst in the hydrolysis of MgATP by the nitrogenase from Amtobarter vinelandii communicated by Cordewener et al. (1987) It was feasible to monitor MgATP-dependent pre-steady-state proton production by the absorbance change at 572 nm of the pH indicator o-cresolsulfonaphthalein in a weakly buffered solution. At 5.6"C, a pre-steady-state phase of H t production was observed, with a first-order rate constant of 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

1992
1992
2005
2005

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…The current paper supplements the preceding communication [9] in which it was shown that the MgATPinduced H + production is much slower than electron transfer. Combined with the results of this paper, a model will be discussed in which the binding of MgATP changes the confor-mation of the protein complex which triggers electron transfer from Fe protein to MoFe protein.…”
supporting
confidence: 64%
“…The current paper supplements the preceding communication [9] in which it was shown that the MgATPinduced H + production is much slower than electron transfer. Combined with the results of this paper, a model will be discussed in which the binding of MgATP changes the confor-mation of the protein complex which triggers electron transfer from Fe protein to MoFe protein.…”
supporting
confidence: 64%
“…In all cases, the Cp2 concentration was 100 M, the Av1 concentration was 75 M, the buffer was 100 mM HEPES, pH 7.4, with 2 mM dithionite, and the samples were incubated for 1 h prior to freezing in liquid nitrogen. All EPR spectra were recorded at 12 K, with a 9.64-GHz microwave frequency, a 6.36-mW microwave power, a 100-kHz modulation frequency, and a modulation amplitude of 5.028 G. mary electron transfer from Cp2 to Av1 in the presence of MgATP represents more than a 10 4 -fold increase from the nucleotide free condition and approaches that observed for the MgATP-dependent rate constants found for the homologous A. vinelandii nitrogenase complex (42).…”
Section: Fig 2 Electron Transfer From the Cp2 [4fe-4s] Cluster To Av1mentioning
confidence: 65%
“…landii ATCC strain 478 was grown and the nitrogenase component proteins were purified and assayed as described elsewhere (15). Specific activities of Av1 and Av2 were at least 8 and 2 mol⅐s Ϫ1 ⅐mol protein Ϫ1 of ethylene produced, respectively.…”
Section: Cell Growth and Isolation And Preparation Of Nitrogenase-a mentioning
confidence: 99%
“…Mensink and Haaker (14) concluded from their experiments on the temperature dependence of the extent and rate of MgATP-induced electron transfer that electron transfer occurs via a highly disordered transition state, which indicates a major conformational change. It was proposed that the binding of MgATP to the nitrogenase complex causes a change of the conformation of the complex that triggers electron transfer (14,15).…”
mentioning
confidence: 99%